Measuring the Impact of Carbon Emissions on Firm Value Using Quantile Regression - Lukas Ferner (Junior Management Science (JUMS), 2019)
A fundamental transformation of the global economy towards a low-carbon economy is inevitable in order to achieve the climate targets set by the United Nations. Hence, it becomes increasingly important to understand how firm level carbon mitigation affects the value of a company. The purpose of this thesis is not only to estimate the average relationship between carbon emissions and firm value but to investigate whether this relationship is heterogeneous and thus whether the effect of carbon emission on firm value depends on the value of the respective company. A quantile regression approach with firm value measured as Tobin's Q as the dependent variable is applied. The estimation outcomes clearly indicate that higher carbon emissions reduce firm value for all quantiles. However, the extent of the effect depends strongly on the value of the respective company suggesting that the value-enhancing effect of reduced carbon emissions is higher for firms with relatively high firm value.
Keywords: 650; carbon emission; firm value; quantile regression